RETRACTED: Melatonin Mediates Osteoblast Proliferation Through the STIM1/ORAI1 Pathway - Cao, Lili; Yang, Keda; Yuan, Wei; Zhou, Siming; Zhao, Rui; Qiu, Shui (Frontiers in Pharmacology, 2022)
Introduction Osteoporosis (OP) is a progressive, systemic bone disease that is one of the main causes of disability and death in elderly female patients. As an amine hormone produced by the human pineal gland, melatonin plays an important role in regulating bone metabolism. This study intends to investigate the relationship between melatonin levels in human blood and bone density and to suggest the efficacy of melatonin in treating osteoporosis by performing in vivo and in vitro experiments. Methods We used liquid chromatography-tandem mass spectrometry to determine the serum melatonin levels in postmenopausal women with osteoporosis and young women with a normal bone mass. The bone density, BV/TV, Tb.Th, Tb.Sp and other indicators of postmenopausal osteoporosis and mice with a normal bone mass were detected by measuring bone density and micro-CT. The intracellular calcium ion concentration was detected using fluorescence microscopy and a full-wavelength multifunctional microplate reader, and the expression of SOCE-related genes and STIM1/ORAI1 proteins was detected using PCR and WB. Results This study confirmed that bone density positively correlates with the melatonin level in human blood. In the animal model, melatonin supplementation reverses postmenopausal osteoporosis. We explored the internal mechanism of melatonin treatment of osteoporosis. Melatonin promotes an increase in intracellular calcium ion concentrations through the STIM1/ORAI1 pathway to induce osteoblast proliferation. Conclusions This study provides an important theoretical basis for the clinical application of melatonin in patients with osteoporosis and helps to optimize the diagnosis and treatment of postmenopausal osteoporosis.